A literature research on the drying quality of agricultural products with using solar drying technologies. (15th November 2021) - Deng, Zhihan; Li, Ming; Xing, Tianyu; Zhang, Junyi; Wang, Yunfeng; Zhang, Ying
Highlights: Prevalent quality assessment of drying materials with solar energy was reviewed. The potential application of solar drying for high-quality dried products was introduced. The physical and chemical mechanisms of quality transformation during drying process were clarified. Abstract: Solar energy is a green and renewable clean energy. Using this as main or auxiliary energy to dry agricultural materials could reduce energy consumption and improve product quality. In the drying process of agricultural materials, not only drying technologies but also drying parameters would affect the quality of materials. This paper provides a guided technological tour on solar drying through a literature research. An overview about the drying technologies to evaluate the drying quality, such as traditional sun drying, solar tunnel drying, solar greenhouse drying, solar-assisted drying system, is presented to demonstrate advances and application potential of solar drying. Finally, variable temperature drying is preliminarily proposed and tested to verify its superiority of energy saving and drying quality improvement. The literature research in this paper gives a reference on the effective application of solar drying through specifying the mechanisms of quality transformation.